SOFTWARE IMPLEMENTATION OF THE METHOD OF CALCULATING THE ENERGY CONSUMPTION OF A BUILDING - SOKOL, KOSTIANTYN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In the conditions of a constant increase in energy prices, the desire to reduce harmful emissions to the atmosphere, as well as the shortage of fossil fuels that can be used for heating, methods of increasing energy efficiency and energy saving attract attention. One of the main characteristics of a building's energy efficiency is its energy consumption - a value that determines the amount of energy that must be spent on heating or conditioning the interior of the building to ensure a comfortable temperature. This work is devoted to the development of the calculation method and its software implementation. In the course of the study, several of the most common methods of heat transfer analysis were developed, in particular, methods of numerical analysis based on the approximation of differential equations and engineering calculation methods using equations describing various mechanisms of heat transfer. Having determined that none of the methods is optimal for solving the set goal, it was decided to synthesize a new method, using the best approaches from all the processed information. The result was the developed method, the basis of which were the formulas for calculating thermal conductivity, convection, thermal radiation, and heat capacity, which in terms of the structure of its implementation is similar to numerical methods, where the calculation progresses gradually along two coordinates: spatial and temporal, and also, in some formulas, there are weights coefficients similar to those used in the finite element method. The calculation is organized in such a way that a more detailed analysis of the building's thermal behavior is also possible. The availability of such a method, as well as the computer system in which it is implemented, will allow to quickly obtain fairly accurate values of the building's energy needs. The characteristics of the computer system make it convenient for use in the design of private and multi-apartment buildings with clear energy efficiency requirements,
Keywords: heat transfer; computer system